A Review of Rural Tourism Development in the Context of Social Exchange Theory Application - Albert, Grace Octavia; Abdul Rashid, Rosmalina; Mojiol, Andy Russel (Department of Forest Resources Conservation and Ecotourism - IPB University, 2024)
Rural tourism promotes sustainable development through economic, socio-cultural, and environmental means. To embrace rural tourism development, communities need to thoroughly evaluate the benefits and drawbacks associated with such changes. The challenges of this process entail assessing the consequences of the decision made in response to the social interactions occurring within the community. This study conducts a systematic review to identify research gaps in the application of Social Exchange Theory (SET), focusing on how attitudes, networking, and participation influence community decisions towards rural tourism. The findings reveal that these factors significantly shape local communities' perspectives and involvement in tourism development. Concluding with a conceptual framework grounded in SET, the paper provides insights into how attitudes, networking, and participation can drive sustainable rural tourism and facilitate cultural heritage conservation.